Innovative approaches to improve serodiagnosis of Strongyloides stercoralis infection - Levenhagen,Marcelo Arantes (2021)
ABSTRACT Strongyloidiasis is a helminthiasis of neglected condition that has no gold standard parasitological diagnosis due to the intermittent release of larvae in feces. This study aimed to use an scFv (single chain variable fragment) obtained by Phage Display, previously validated to detect immune complexes in serum samples from individuals infected with Strongyloides stercoralis by enzyme-linked immunosorbent assay (ELISA). Now the ability of scFv to detect the immune complexes was verified by immunofluorescence, flow cytometry using magnetic beads and surface plasmon resonance (SPR). As ELISA, the SPR, immunofluorescence and flow cytometry demonstrated the ability of scFv to detect immune complexes in sera from individuals with strongyloidiasis and discriminate them from sera of individuals with other parasitic diseases and healthy individuals. Besides de conventional ELISA, the novel approaches can also be promptly applied as auxiliary diagnostic tools to the existing parasitological method for accurate diagnosis of human strongyloidiasis.